The Association Between Midlife Leisure-Time Physical Activity and Hearing Loss in Late Life in the Atherosclerosis Risk in Communities Study - Martinez-Amezcua, Pablo; Garcia Morales, Emmanuel; Gabriel, Kelley P; Dooley, Erin E; Hornikel, Bjoern; Coresh, Josef; Lin, Frank R; Pankow, James S; Sharrett, A Richey; Schrack, Jennifer A; Sullivan, Kevin J; Reed, Nicholas; et al. (The journals of gerontology. Series A, Biological sciences and medical sciences, 2023)
Hearing loss is highly prevalent in older ages and has several health consequences. Some cardiovascular risk factors are associated with worse hearing at older ages. Still, the role of midlife leisure-time physical activity (PA) as a risk factor for hearing loss is yet to be investigated. Among 3 198 participants of the Atherosclerosis Risk in Communities study, we investigated the associations of midlife and change from mid- to late-life PA (assessed via modified Baecke questionnaire) with hearing loss (audiometric battery [worse-ear pure-tone average, and speech-in-noise test]) at older ages. We used regression analyses, adjusted for demographics, medical conditions, and noise exposure, to estimate differences in hearing between those who met and did not meet PA recommendations at midlife and at late life. A total of 1 386 (43.3%) participants met PA recommendations at midlife. These participants, compared to those who did not meet recommendations, had lower (better) pure-tone average by 1.51 (0.46, 2.55) decibels, identified 0.37 (0.01, 0.74) more words (better score) in the speech-in-noise test, and had a lower relative risk of having hearing loss at older ages (eg, relative risk ratio for severe hearing loss vs normal hearing = 0.70 [0.52, 0.95]). Similarly, those who persistently met PA recommendations from mid- to late life had, compared with those who did not, a better hearing at older ages. Meeting PA public health recommendations in midlife and mid- to late life was associated with better hearing at older ages and reduced risk of hearing loss. Promoting adequate levels of PA may be an essential component of hearing care.